The magic of tinned fish : elevate your cooking with canned anchovies, sardines, mackerel, crab, and other amazing seafood - McDade, Chris (Artisan Books, 2021)
"Whether mixed with mayonnaise to make a salad or infused in a tomato sauce and served over pasta, tinned fish are an economical and flavorful addition to most anything you cook. Tinning fish is an old-world preservation method that gives us modern convenience. These fish-anchovies, mackerel, sardines, octopus, and squid, among others-are packed at their peak of freshness, meaning you get all the flavor at a fraction of the cost of buying fish fresh. The 75 recipes range from the simplest snack (try sardines on a Wasa cracker with mustard and lemon) to dishes for holiday entertaining (like a lamb roast studded with anchovies and served with rosemary roasted potatoes). Also included are weeknight pastas, such as Spaghetti with Smoked Oysters and Egg Yolks, and even a meat lover's favorite Steak with Anchovy Butter. Tinned fish are a natural part of an outdoor picnic spread-anchovy, bread, and butter make the perfect sandwich-but they can also be served at a party, especially a warm Cod Brandade on toasts. Tinned fish are perfectly on trend and for good reason: they're sustainable, economical, full of variety, and a great choice to keep stocked in your pantry"--